2021
DOI: 10.3390/vaccines9020096
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Inactivated Acinetobacter baumannii Vaccine Candidates

Abstract: Acinetobacter baumannii is a bacterial pathogen that is often multidrug-resistant (MDR) and causes a range of life-threatening illnesses, including pneumonia, septicemia, and wound infections. Some antibiotic treatments can reduce mortality if dosed early enough before an infection progresses, but there are few other treatment options when it comes to MDR-infection. Although several prophylactic strategies have been assessed, no vaccine candidates have advanced to clinical trials or have been approved. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…In each instance, the CFU per mL of MRSA-M2 was over 1 × 10 9 initially and declined to zero after a 100 s exposure, indicating rapid and complete inactivation. For each of the preparations, the inactivation kinetics was equivalent in the presence or absence of MDP, indicating that MDP did not enhance survival, consistent with previous observations that MDP does not protect against direct nucleotide damage [25,26,32]. A five-minute UVC exposure was selected for subsequent in vitro and in vivo experiments to give a large safety margin.…”
Section: Presence Of Mdp During Uvc Irradiation: Effects On Bacterial...supporting
confidence: 77%
See 1 more Smart Citation
“…In each instance, the CFU per mL of MRSA-M2 was over 1 × 10 9 initially and declined to zero after a 100 s exposure, indicating rapid and complete inactivation. For each of the preparations, the inactivation kinetics was equivalent in the presence or absence of MDP, indicating that MDP did not enhance survival, consistent with previous observations that MDP does not protect against direct nucleotide damage [25,26,32]. A five-minute UVC exposure was selected for subsequent in vitro and in vivo experiments to give a large safety margin.…”
Section: Presence Of Mdp During Uvc Irradiation: Effects On Bacterial...supporting
confidence: 77%
“…To overcome epitope damage, we have developed a method: irradiation in the presence of the powerful antioxidant manganese-decapeptide-phosphate (MDP), derived from the extreme radioresistant bacterium Deinococcus radiodurans. When bacteria are mixed with MDP and exposed to supralethal doses of γ-rays or UVC irradiation, their genomes are destroyed, but antigenic epitopes remain intact [25,26]. In the presence of MDP, the epitopes are protected and can still stimulate immune protection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gamma-irradiated S. pneumoniae vaccine produced after inactivation with 10 kGy gamma irradiation elicits strong mucosal and systemic immune responses in mice model, which is indicative of the affectivity of gamma irradiation as a method for the development of a killed whole-cell pneumococcal vaccine ( 21 ). Furthermore, sterilization doses for radiation-sensitive organisms could be significantly reduced, which would be expected to reduce damage to epitopes required to develop a protective immune response while maintaining an adequate margin of safety to ensure complete inactivation ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…). An inactivated whole-cell vaccine derived from antibiotic-exposed MDR A. baumannii (I-M28-47-114) (Shu et al 2016) and radiation inactivated cells were found to be protective (Dollery et al 2021).…”
Section: Whole Cell Vaccinesmentioning
confidence: 99%